Radial sphincterotomy in endoscopic retrograde cholangiopancreatography due to extrahepatic obstructions by large stones in the common bile duct - Kenan Yusif-zade (Fujita Medical Journal, 2021)
Objectives: The most common method of removal of calculi (“stones”) from the common bile duct (CBD) is an endoscopic sphincterotomy. We wished to determine the role of an improved method of sphincterotomy in choledocholithiasis: “radial sphincterotomy”.